Exploring Operational Managers’ logic around trade-offs related to sustainability - Daubenschuez, Tobias (Auckland University of Technology, 2010)
This dissertation investigates how managers perceive trade-offs in relation to sustainability. The dissertation results from a research project with both a theoretical and applied orientation, following the argument that both in business and in theory, a “win-win paradigm” of sustainability prevails. According to the win-win paradigm, the extent of a company’s environmental and social commitment is principally restricted by its positive economic value. Drawing on a practical case, this dissertation contributes to this new and underexplored field of research around the win-win paradigm of sustainability. The dissertation 1) investigates the win-win paradigm with regard to the business case to be made for adoption of a particular initiative; and 2) explores operational managers’ logic around trade-offs related to sustainability. Academic and practitioner literature regarding sustainability, the win-win paradigm and sustainability-related trade-offs was reviewed, as was the context for business decisions. Data collection was based on in-depth interviews with operational managers from four different companies with an interest in a particular sustainability initiative. The data were analysed thematically and integrated with the afore-mentioned literature to inductively develop a series of hypotheses. The dissertation confirms that companies are trapped within the limits of the win-win paradigm of sustainability. Externally-oriented initiatives are regarded as more likely to overcome financial boundaries than are internally-oriented initiatives. It is found that the specifics of an industry determine the scope of the win-win zone for companies. The dissertation moreover argues that competitive forces reinforce the boundaries of the win-win paradigm and that the win-win zone is likely to expand in future in the particular initiative at the centre of this dissertation. Visible problems, which affect companies in exploiting their environmental and economic (win-win) opportunities, can be grounded in the hidden context of stakeholder-related trade-offs. These trade-offs stem from a lack of incentives for involved stakeholders. The recognition of these trade-offs is impeded by a lack of communication.
Keywords: Sustainability; Trade-offs